BERTUKAR KURSI, BERTUKAR HATI: TRANSFORMASI PELAYANAN PASTORAL MELALUI TEKNIK ROLE REVERSAL - Matheos Kanalung; Yohan Brek (MATHESI: Jurnal Pendidikan dan Bimbingan Konseling, 2026)
Communication breakdown in pastoral counseling is often caused by the client's self-defensemechanisms and rigid egocentrism, where individuals become trapped in a victim mindset and fail toperceive the humanity of others. This study aims to explore the effectiveness of Jacob L. Moreno’s RoleReversal technique as an instrument for spiritual and emotional transformation in pastoral care.Utilizing a qualitative-descriptive approach with a theological literature review, the findings indicatethat this technique is not merely a role-play but a means of kenosis (self-empty) that emulates Christ'sincarnational model. Cognitively, the technique breaks biases and prejudices; emotionally, it evokescompassion through affective resonance; and spiritually, it facilitates forgiveness by re-humanizingothers as Imago Dei. In conclusion, "exchanging chairs" enables a profound metanoia (renewal of themind), transforming relational conflicts into a space of transformative reconciliation under theguidance of the Holy Spirit.